Investigation on the Mechanical Properties of TIG Welded AA6061 Alloy Weldments using Different Aluminium Fillers - L. H., Shah; Nur Azhani, Abd Razak; Juliawati, Alias; M., Ishak (Global Science and Technology Forum, 2013)
In this research, the effect of filler weld material on the mechanical properties of tungsten inert gas (TIG) welded AA6061 alloy weldments have been investigated. The microstructure of the base metal (BM) as well as weld metal (WM) and heat affected zone (HAZ) was analyzed using optical microscopy and scanning electron microscopy (SEM), and the Vickers hardness of the samples were compared. Corrosion resistance of the weld area was investigated in natural seawater solution. Results for both filler samples indicate that the strength of the WMs and HAZs is lower compared to BMs. In addition to that, the weld joints of ER4043 samples show relatively higher hardness compared to ER4047 samples. The corrosion test results show that ER4043 sample has a lower corrosion rate value compared to ER4047. It can be concluded that ER4043 samples show better Vickers hardness value and corrosion resistance compared to ER4047 samples.